(untitled) (Research, Society and Development, 2021)
In order to diagnose, classify and associate the degree of stenosis of the nostrils to epidemiological parameters, 134 brachycephalic dogs treated at the Narizinho Project -UFF were evaluated. Of these, 79 (59%) were males and 55 (41%) females, with more intense stenosis being observed in 58/79 male individuals (73%). The average age of the animals was 2.7 years, where seventy-five percent of individuals between two and six years of age had severe stenosis of the nostrils. The dogs admitted belonged to the French Bulldog, English Bulldog, Pug and Shih tzu breeds, with the majority of the dogs 90/134 (67%), classified with severely drawn nostrils. The French Bulldog breed had the highest percentage of specimens with the most intense level of stenosis of the nostrils 72% (57/79). All Pug animals were diagnosed with stenotic nostrils, the second most prevalent breed with severe nostril obstruction 62% (23/37). Among English bulldogs, 50% had severely narrowed nostrils. The Shih Tzu breed showed the highest percentage of individuals without stenosis, 36% (5/14), despite the fact that most individuals had a severe nostril obstruction 57% (8/14). The different degrees of stenosis of the nostrils causing the obstruction of the anterior airways in brachycephalic dogs is associated with breed and age, hindering the normal flow of air to the lungs, thus directly impacting the clinical symptoms and quality of the animals.